Analisis Penilaian Kinerja Guru Menggunakan Metode Multifactor Evaluation Process Melalui Key Performance Indikators di SD Negeri 2 Selat Panjang - Suliana; Nasien, Dewi; Tatminingsih, Sri (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This research is driven by various issues related to the quality of teacher performance at SD Negeri 2 Selat Panjang, which include 1) the low educational qualifications of teachers who have not yet attained a bachelor's degree (S1/D4); 2) limited skills in writing and publishing scientific papers; 3) low participation and experience in academic forums; and 4) low levels of academic achievement among teachers. Therefore, this study aims to: 1) Analyze the results of a teacher performance evaluation using the multifactor evaluation process method through key performance indicators at SD Negeri 2 Selat Panjang, and 2) Develop strategies for improving teacher performance at SD Negeri 2 Selat Panjang based on the results of the multifactor evaluation process. This research employs a descriptive quantitative approach. The population consists of all 25 teachers at SD Negeri 2 Selat Panjang. Data collection techniques include field observation, expert opinion, performance assessment questionnaires, and the calculation of teacher performance levels, which are then analyzed descriptively. The results indicate that: 1) The performance scores of the 25 teachers at SD Negeri 2 Selat Panjang range from 20, categorized as very poor, to 40, categorized as poor; 2) The average scores for academic competence, academic achievement, professional development activities, and participation in scientific forums are 21.36, 6.00, 5.25, and 8.08, respectively; 3) The overall performance score of the teachers at SD Negeri 2 Selat Panjang is 40.68, categorized as poor; and 4) Enhancing teacher performance at SD Negeri 2 Selat Panjang requires collaborative efforts between the teachers and the principal.